The Influence of Learning Independence and Time Management on The Sciences Learning Outcomes of Class VIII Students of SMP Negeri 5 Pematang Siantar - Tirta Anastasia (MultiTech Publisher, 2023)
The aim of this research was to determine the influence of learning independence and time management on social studies learning outcomes for class VIII students at SMP Negeri 5 Pematang Siantar. This research uses a quantitative type of research with a quantitative descriptive data analysis approach. Class VIII students of SMP Negeri 5 Pematang Siantar with a total of 186 students constitute the population in this study. Sampling in this study used the proportional allocation formula technique. Using sampling techniques in this research, there were 127 people consisting of classes VIII-1, VIII-2, VIII-3, VIII-4, VIII-5 and VIII-6. Data collection techniques use questionnaires and documentation. The hypothesis making technique uses multiple linear regression analysis. The results of this study show that: 1) There is a positive and significant influence of learning independence on student learning outcomes, seen from the significance value in the t test results of 0.000 ˂ 0.05, and the t test where the calculated t value of learning independence is (3.954) ˃ t table (1.65694) which means that this variable is significant. 2) There is a positive and significant influence of time management on student learning outcomes, seen from the t test where the calculated t value of time management is (3.857) ˃ t table (1.65694) which means that this variable is significant. 3) Learning independence and time management together influence learning outcomes, seen from the F test where the calculated F value is (23.755) ˃ table F value (3.067). The R square coefficient of determination test was found to be 0.277, which means that 27.7% of the learning independence and time management variables influence student learning outcomes at SMP Negeri 5 Pematang Siantar and the remaining 72.3% is the influence of other variables not examined in this research. The regression value is 1920.882, while the residual value is 5013.544, which means there are other factors that influence learning outcomes but were not studied in this study, namely 5013.544. The results of the multiple regression analysis test are Y = 29.426+ 0.372+0.373, which means that variable X2 (time management) with a value of 0.373 has a more dominant influence than variable X1 (independence in learning) with a value of 0.372.